Decolonizing the teaching of foreign languages in multicultural communities: a case study of the teaching of English in Togo (West Africa) - Tarno Akponi (Language and Semiotic Studies, 2025)
This study investigates the inputs of multicultural awareness in the teaching of English as a foreign language in Togo. It posits that in multicultural contexts, the teaching and learning of foreign languages face various challenges. These challenges can be successfully raised through an integration of local cultural elements while developing English learning materials. The study employed a structured questionnaire which was administered to 320 students and 8 lecturers from the two Togolese public universities. It also used interviews and classroom observations to access the English language teaching/learning system in Togo. The study is anchored on Vygotsky’s Social Constructivism Theory, which propounds that language and culture play essential roles both in human intellectual development and in how humans perceive the world. The analysis of the data showed that in a multicultural context, the designing of foreign language textbooks and learning tutorials and, classroom activities require an inclusion of foreign and local realities such as language features, culinary system, proverbs, stories and folktales, traditional festivals, and wedding celebration. The integration of local material and non-material culture help reduce student’s fear and anxiety in English language classrooms and boost their willingness to learn the language.